Neglected Achilles tendon ruptures: literature review - Leite, Raul Prioli; Sossa, Felipe Ayusso Correa; Santos, João Paulo Gonçalves dos; Osório Neto, Ernane Bruno; Queiroz, Marcel Rolim; Macedo, Rafael da Rocha (Journal of the Foot & Ankle, 2025)
Objective: Review the literature on the current treatment of neglected Achilles tendon ruptures, their results, and potential complications. Methods: Bibliographic review on the state of the art in national and international databases. Articles published in indexed journals between 1991 and 2022 that addressed the treatment of Achilles tendon ruptures with more than four weeks of evolution were selected; however, only articles with less than 22 years of publication (2000-2022) were analyzed. Results: Surgical treatment is well-established in patients with significant functional demands. The various surgical techniques described in the literature and currently used have similar success rates and complications, especially regarding patient satisfaction, functional results, anthropometric measurements, and return to work and sports activities. Conclusion: Several techniques can be used to treat neglected Achilles tendon ruptures. When choosing the most appropriate technique, gap size, patient characteristics, and surgeon experience should be considered. Level of evidence I; Type of study; Evaluation of results.